Aspek Perpajakan Kantor Perwakilan Perusahaan Perdagangan Asing ABC (Thailand) - Khomara, Rania; Sandra, Amelia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
Globalization has encouraged the growth of foreign investment in Indonesia, including the establishment of foreign trade company representative offices (KP3A) such as ABC in 2022. This study aims to analyze the treatment of Income Tax withholding and collection, self-paid Income Tax, VAT/Sales Tax on Luxury Goods, and Local Taxes at the ABC representative office. KP3A, as a form of foreign company representative office (KPPA), is mandated only to manage the interests of its parent company abroad and is prohibited from conducting business or generating income in Indonesia, which affects its obligation to file Annual Tax Returns. The findings confirm that KP3A ABC fulfills its tax obligations in accordance with Indonesian regulations, yet the rules concerning Annual SPT reporting remain uncertain and require clearer guidance to ensure legal certainty for taxpayers.